Morphology of the larval mandible and maxilla in the subgenus Carrollia Lutz of Culex L. (Diptera: Culicidae) - Liria, Jonathan; Navarro, Juan-Carlos (Zootaxa, 2003)
Larval mouthpart morphology has proven to be an additional taxonomic tool at the subgeneric and generic level in mosquitoes (Diptera: Culicidae) of the genus Anopheles and some members of the tribe Sabethini. However, little is known about these characters in genus Culex. The present work describes the mouthpart morphology of four species belonging to the recognized groups in the subgenus Carrollia. Five mandibular characters are diagnostic in the subgenus, four on the mandible and one on the maxilla: posterior dorsal tooth (PDT), mandibular comb (MnC), mandibular spiculose area (MSA), postartis (Poa) and dorsal maxillary suture (DMxS). The maxilla offers two characters that allow the separation of the groups proposed by Valencia (1973) for this taxon: seta (4- Mx), Cx. bihaicola and Cx. rausseoi (bihaicola group) is large (0.127-0.159 mm), little sclerotized, not branched and located posterior beyond the laciniarastrum one (LR1), in Cx. iridescens and Cx. urichii (iridiscens group) it is very large (0.203-0.229 mm), strongly sclerotized, branched on the apex and medial to the maxillary body (MxBo).